Implementasi Nilai-Nilai Moderasi Beragama Dalam Kurikulum Pendidikan: Upaya Pencegahan Radikalisme Sejak Dini - Firdaus Fauzi (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
Radicalism in the world of education has become a serious issue that has the potential to disrupt social stability and community diversity. This article discusses the implementation of religious moderation values in the education curriculum, particularly at the elementary school and madrasa levels, as a preventive measure against the early spread of radical ideologies. This research uses the literature study method by analyzing various sources of literature related to Islamic religious education, radicalism, and religious moderation. The research results show that educational institutions play a strategic role in instilling values of moderation such as tolerance, justice, balance, and compassion in students. Islamic religious education should not only teach doctrine but also emphasize the implementation of religious values in real life. The development of a curriculum that incorporates moderation values is important for shaping students' characters to be inclusive and open to differences. The role of the government and schools is crucial in developing a curriculum oriented towards strengthening the culture of religious moderation as a concrete effort to prevent the spread of extremism in the educational environment from an early age.